Need for cognitive closure, political trust, and belief in conspiracy theories during the COVID-19 pandemic - Jedinger, Alexander; Masch, Lena (Frontiers in Social Psychology, 2025)
IntroductionThis research examines the effect of individual differences in the need for cognitive closure and political trust on the endorsement of COVID-19 conspiracy theories. We hypothesize that individuals high in cognitive closure and low in political trust will seize on conspiracy accounts of the pandemic. In contrast, we expect that individuals high in cognitive closure and political trust are more likely to disregard conspiracies surrounding the COVID-19 pandemic.MethodTo test our preregistered hypotheses, we rely on data from multiple waves of a representative survey among the German population (N = 2,883). The need for cognitive closure and general political trust was assessed before the beginning of the COVID-19 pandemic, while belief in COVID-19 conspiracy theories and specific trust in handling the crisis was fielded during the second wave of the pandemic.ResultsWe find that individuals with a high need for cognitive closure are more likely to accept conspiracy narratives, but the effect size is small. At the same time, pre-pandemic trust and concurrent trust in political and medical institutions are strongly negatively related to conspiracy beliefs. We find no support for a moderating effect of political trust.ConclusionThis study finds only small effects for individual differences in the need for cognitive closure but strong effects for political trust in explaining conspiracy beliefs. It underlines the importance of a lack of trust in political institutions for democratic societies in the age of misinformation and post-truth politics.